Amphifunctional Mesoporous Silica Nanoparticles with "Molecular Gates" for Controlled Drug Uptake and Release. (23rd November 2021) - Shinde, Pravin; Prasad, Bhagavatula L. V.
Abstract: It is demonstrated that the uptake and release of hydrophobic drugs/dyes by mesoporous silica nanoparticles (MSN) is critically dependent on the functional groups present on their outer surfaces. For this, amphifunctional MSNs are synthesized, possessing hydrophobic pores and hydrophilic functional groups on the outer surface. Further, the outer surface is modified with a different chain length of molecules, e.g., propargyl alcohol, triethylene glycol, and PEG (2000) via azide–alkyne click chemistry. The effect of these different surface functional groups on uptake of drug/dye is demonstrated with Nile red, proflavine (free base form), and rhodamine 6G. The uptake of these molecules is found to be inversely proportional to the bulkiness of surface functionality. To counter this effect, an alternate method of loading is proposed and demonstrated. Finally, the effect of these different functional groups on the release of loaded drug proflavine is studied, which supports the hypothesis that bulkier outer surface groups also hinder the release of drugs loaded in the porous MSN. Abstract : Pore entrances of mesoporous silica nanoparticles modified with "molecular gates" of increasing bulkiness display uptake/release of drug that is directly influenced by the bulkiness of outer surface group.